2013
DOI: 10.3329/bjms.v12i3.15423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status among Adolescent Garo in Sherpur District, Bangladesh

Abstract: Background: Garo is one of the largest indigenous communities of Bangladesh. Adolescence is a golden period of time for nutritional promotion. Adolescent nutrition did not receive adequate attention in Bangladesh. Tribal people like the Garo are even more unaware about the importance of adolescent nutrition. Objectives: To find out physical growth as well as nutritional status among adolescent Garo children in Sherpur district on the basis of anthropometric indices. Methods and materials: This cross sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
(2 reference statements)
0
8
2
Order By: Relevance
“…Similarly, the prevalence of stunting in the current study was lower than in the study conducted at the Amhara Region [ 17 ] and in Adwa, northern Ethiopia [ 20 ]. The prevalence in this study were also lower than those reported from a study conducted in Bangladesh [ 19 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Similarly, the prevalence of stunting in the current study was lower than in the study conducted at the Amhara Region [ 17 ] and in Adwa, northern Ethiopia [ 20 ]. The prevalence in this study were also lower than those reported from a study conducted in Bangladesh [ 19 ].…”
Section: Discussioncontrasting
confidence: 86%
“…In this study, socio-economic status, maternal working status, family type, and family size were important determinants of nutritional status of adolescents. 32 The prevalence of thinness was also 37.8% and 58.3% in a study conducted in the rural community of Tigray and Mekelle city. 32 , 33 A study conducted in India, South Ethiopia, Ambo, Tigray, and Northwest Ethiopia revealed that age is independently associated with nutritional status of adolescent girls.…”
Section: Introductionmentioning
confidence: 92%
“…Underweight and obesity prevention in children and adolescents is a major priority of governments worldwide including in Indonesia,26, 27 where the prevalence of being underweight and overweight in school-aged children is around 14.5% and 20.4%, respectively 28 . Many factors contribute to the occurrence of malnutrition (underweight and overweight) in adolescents, such as a lack of macro and micronutrient consumption, breakfast habits, adequate hours of sleep, socio-economic status, physical activity, and well-balanced nutrition 28, 29, 30, 31…”
Section: Discussionmentioning
confidence: 99%